1995
DOI: 10.1007/bf00838482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of an ambulatory teaching/treatment programme for non-insulin dependent (type 2) diabetic patients

Abstract: The aim of this study was to evaluate the effect of a structured teaching/treatment programme on the clinical and metabolic control of non-insulin-dependent (type 2) diabetic patients. The programme was aimed at improving the overall treatment quality in these patients through measures involving self-care, diet, exercise and weight reduction. Four theoretical-practical teaching units were given once a week to group of 5-8 ambulatory patients by previously trained general practitioners. Clinical and biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 16 publications
(11 reference statements)
2
20
0
4
Order By: Relevance
“…Following the selection criteria of the reviews, 16 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] referring to our three reference programmes should have been identified. In practice, a total of 11 were identified [5,28,30,32,34,38,39,[43][44][45][46], and seven [28,32,34,35,38,39,46] were included in at least one of the reviews. In six reviews the main controlled trials of our reference programmes [28, 30-32, 38, 44] were included in data synthesis [10,11,16,18,19,25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the selection criteria of the reviews, 16 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] referring to our three reference programmes should have been identified. In practice, a total of 11 were identified [5,28,30,32,34,38,39,[43][44][45][46], and seven [28,32,34,35,38,39,46] were included in at least one of the reviews. In six reviews the main controlled trials of our reference programmes [28, 30-32, 38, 44] were included in data synthesis [10,11,16,18,19,25].…”
Section: Resultsmentioning
confidence: 99%
“…In six reviews the main controlled trials of our reference programmes [28, 30-32, 38, 44] were included in data synthesis [10,11,16,18,19,25]. Out of 25 [5, 33-37, 39, 41-43, 45-59] replication trials (phase 4, see text box: Phases of 'increasing evidence of complex interventions') four [34,35,39,46] were included in six reviews [16,19,21,22,24,25]. Different reviews on identical topics included different publications referring to the same reference programme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impossibility to clearly separate interventions according to these criteria is reflected by the handling of three publications on an identical intervention that is the group treatment and teaching programme for patients with Type II diabetes as described in the present article. The review included the publication by Pieber et al [47], but not those by Kronsbein et al [46] and Domenech et al [48]. All three studies had a similar study design.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improvement of triglyceride concentrations, glycosylated haemoglobin concentrations were reduced by almost 1% and blood pressure was lowered. In a further 1-year prospective controlled trial with comparable results, it was shown that the programme was transferable to Argentina [48]. For this latter project the teaching materials were translated and adapted to the special cultural conditions of Latin America.…”
Section: Replication and Transferabilitymentioning
confidence: 99%